Pengaruh Iklim Organisasi dan Work Life Balance terhadap Kinerja Guru SMPN 1 Petasia - Nurhalisa Nurhalisa; Niluh Putu Evvy Rossanty; Andi Indriani Ibrahim; Muh. Zeylo Auriza (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of organizational climate and work-life balance on the performance of SMPN 1 Petasia teachers in North Morowali Regency. The background of this research is based on the importance of the role of teachers as the main actors in improving the quality of education, whose performance is influenced by internal and external factors. A conducive organizational climate and work-life balance are seen as two important variables that can affect teachers' productivity and professionalism. This study uses a quantitative approach with the type of associative research. The sample of 40 teachers was determined through saturated sampling techniques. Data collection was carried out through questionnaires, observations, interviews, and documentation. Data analysis used multiple linear regression with F test, t-test, and determination coefficient. The results of the study show that the organizational climate and work-life balance simultaneously have a positive and significant effect on teacher performance. Partially, both variables also make a positive contribution, where the organizational climate supports the creation of a productive work environment, and the work-life balance maintains motivation and consistency in the implementation of tasks. These findings provide important implications for school and local government policymaking in supporting the professionalism of educators through strengthening organizational aspects and individual welfare.